(F)airwaves a study on gender equality in Metro Manila radio newsrooms - Wu, Eunice Lei Sta. Maria 1997- (University of the Philippines Diliman, 2018)
"This research examined the question of how gender equal Metro Manila radio newsrooms are. The 2010 Global Media Monitoring Project spearheaded by Who Makes the News cited a dominance of men in the Philippine radio industry compared to women as well as a disparity in the topics covered by the genders. For this study, eight radio stations in Metro Manila from a Nielsen Radio Audience Measurement top 10 list in 2017 were analyzed. The theories used were an integration of the muted group theory and feminist communication theories. Surveys among the women and men of the station as well as interviews with the women, management, and human resource personnel, illustrate that many of them held the perception that gender equality existed in their stations. However, problematic notions regarding gender and women still pervades among the interviewees, management and human resources themselves. Data shows that most stations do not conduct gender sensitivity trainings and that interest among the staff in gender issues is relatively low. Women interviewees have also expressed concerns that point to the industry's incapacity to address the special needs that women radio practitioners have to face."